2022
DOI: 10.1002/pbc.29738
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia and not undernutrition predicts high‐dose methotrexate‐induced nephrotoxicity in children with acute lymphoblastic leukemia in resource‐constrained centers

Abstract: Background:The standard practice to mitigate high-dose methotrexate (HD-MTX)induced nephrotoxicity (HMN) in acute lymphoblastic leukemia (ALL) is to monitor levels until serum MTX falls below a predefined threshold. It is not feasible in most resource-constrained centers. Literature on the various factors affecting HMN in these centers is limited, retrospective, and heterogeneous. Though hypoalbuminemia has been postulated as a risk factor for HMN, the relationship of undernutrition with HMN has not been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Despite the establishment of optimal supportive care, HDMTX poses the risk of devastating complications. HDMTX-induced nephrotoxicity typically occurs in approximately 10% cases, [17,20,23] with single studies reporting nephrotoxicity rates as high as 38%. [30] These adverse effects pose a greater challenge to adult patients with lymphoma, who are commonly over 70 years of age and have multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the establishment of optimal supportive care, HDMTX poses the risk of devastating complications. HDMTX-induced nephrotoxicity typically occurs in approximately 10% cases, [17,20,23] with single studies reporting nephrotoxicity rates as high as 38%. [30] These adverse effects pose a greater challenge to adult patients with lymphoma, who are commonly over 70 years of age and have multiple comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies on HDMTX have predominantly focused on pediatric and adolescent patients with acute lymphoblastic leukemia (ALL) or osteosarcoma. [8,9,[17][18][19] Even studies involving elderly cohorts often include a mix of lymphoma and solid tumors, [5,10,13,20,21] which compromises the direct application of ndings to these more vulnerable populations. For instance, con icting results have been reported regarding MTX concentration and renal function, with no relationship reported only in childhood ALL.…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistically significant difference in adverse effects seen between the two groups, with the exception of cases with renal impairment. 17 Khera et al concluded that hypoalbuminemia and solitary serum MTX levels predict HDMTX-induced nephrotoxicity in centers where serial MTX level monitoring is not feasible. 18 Mohassel et al conducted another trial on 510 cases and found that there were 204 adult patients and 106 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%